(untitled) (Agroindustria, Sociedad y Ambiente, 2025)
Onion (Allium cepa L.) is the second vegetable with 30% of the world production. Taking into account the importance of knowledge, this study was proposed to study the growth, development and production patterns of three short-day onion cultivars Campo Lindo, Hybrid Granex 429 and the variety Texas Grano 438. Transplantation to the field was carried out when the seedlings reached a thickness of 0.5 centimeters, a height of 12 to 15 centimeters and developed four leaves. The design used was in completely randomized blocks with 4 repetitions. The variables evaluated were: Survival percentage, plant height, number of leaves, average weight of bulbs at harvest and yield expressed in Kg/ha. The highest survival percentage was obtained by the variety Texas Grano 438, followed by Campo Lindo and finally the hybrid Granex 429. Regarding plant height, the cultivars Texas Grano 438, Granex 429 and Campo Lindo expressed heights of 63.63, 50.7 and 41.14 cm respectively. For the number of leaves Granex 429 and Texas Grano 438 showed similar values. Regarding the average weight of the bulbs/m2, the variety Texas Grano 438 showed the lowest weight. Regarding yield, the hybrids Campo Lindo and Granex 429 obtained higher and similar yields, surpassing the variety Texas Grano 438. The hybrid Campo Lindo and Granex 429 is recommended because it is a short-day material widely used by farmers in the area.